This is not my story - Uytdewilligen, Ryan, 1992-; Huyck, David, 1976- (Toronto, ON : Kids Can Press, 2023)
This hilarious and unique take on metafiction offers a behind-the-scenes look at the creative process as the hero of this book embarks on a genre-bending journey to find the right story with the help of the author.
Keywords: Creative writing -- Juvenile fiction; Authorship -- Juvenile fiction; Humorous stories; Picture books; Creative writing -- Fiction; Authorship -- Fiction; Humorous stories; Picture books; Romans, nouvelles, etc. pour la jeunesse; Romans, nouvelles, etc. pour la jeunesse; Livres d'images.; picture books; Authorship; Creative writing; Humorous stories; Picture books; picture books; Fiction; Juvenile works; Picture books; Picture books; Livres d'images.